Chromosomal mapping and refinement of the localization of a glaucoma gene at 2cen-2q12 in a Peruvian family: Advances towards the identification of the GLC1B gene - Guevara-Fujita, María Luisa (2022)
Molecular genetics is an important tool to elucidate the cause of hereditary diseases. One of the strategies used in this type of studies, is to map the gene responsible of the disease to a specific chromosome region. This has helped in the characterization of some genes, but others remain to be identified. Primau Open Angle Glaucoma (POAG) is a hereditary disease that can lead to blindness if untreated. There are six loci for POAG: GLClA on chromosome region lq24.3-q25.2, GLClB (2cenq13), GLClC (3q21-q24), GLClD (8q23), GLClE (10p14p15) y GLClF (7q35-q36). In a study of several POAG Peruvian families we have characterized one that cosegregates with markers of chromosome 2 corresponding to a new reported family for GLCIB located at 2cen-2q13. One additional individual in the family reveals genetic recombination that refines the position to a smaller region in 2cen-q12 eliminating several millions of base pairs in the search of the GLCIB gene.